GE_GERICHTE P/10824/2021 vom 18. Oktober 2024 - GE Cour de justice (2024)
VIOL;CONTRAINTE SEXUELLE;ABUS DE LA DÉTRESSE;CLASSEMENT DE LA PROCÉDURE;RAPPORT DE SUBORDINATION | CP.190; CP.189; CPP.319; CP.193